2010
DOI: 10.1161/circulationaha.109.909473
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Microparticles Enhance the Vasoregenerative Potential of Angiogenic Early Outgrowth Cells After Vascular Injury

Abstract: Background-Angiogenic early outgrowth cells (EOCs) have been reported to contribute to endothelial regeneration and to limit neointima formation after vascular injury. Vascular pathologies comprise platelet activation and concomitant generation of platelet microparticles (PMPs). We hypothesized that PMPs may interact with EOCs in the context of vascular injury and modulate their regenerative potential. Methods and Results-Using flow cytometry, confocal microscopy, and scanning electron microscopy, we demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
179
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 187 publications
(190 citation statements)
references
References 36 publications
(43 reference statements)
6
179
1
1
Order By: Relevance
“…It was reported that platelets and platelet microparticles could support the integrity of the endothelium. [25][26][27] In this study, when platelets were added to cultured HUVECs, endothelium viability was enhanced and cell apoptosis was highly suppressed. Our data support the promotion of cell survival via platelet internalization.…”
Section: Discussionmentioning
confidence: 79%
“…It was reported that platelets and platelet microparticles could support the integrity of the endothelium. [25][26][27] In this study, when platelets were added to cultured HUVECs, endothelium viability was enhanced and cell apoptosis was highly suppressed. Our data support the promotion of cell survival via platelet internalization.…”
Section: Discussionmentioning
confidence: 79%
“…MPs obtained from in vitro activated platelets increase the ability of 7-day cultured angiogenic early outgrowth cells (which exhibit phenotypic features of myeloid and endothelial cells and are known as EPCs) isolated from peripheral blood to regenerate vascular injury. 51 These effects include changes in the phenotype of these cells such as increased expression of the endothelial markers (CD31 and vascular endothelial-cadherin) and CXCR4, indicating their maturation toward endothelial cells. Furthermore, platelet MPs enhance Akt activation in response to CXCL12 on angiogenic early outgrowth cells, suggesting a sensitization of CXCR4 pathway by platelet MPs.…”
Section: Mps and Epc Functionmentioning
confidence: 99%
“…50 Also, treatment with platelet MPs increases EPC homing at the sites of vascular injury and proliferation of mature endothelial cells through a mechanism implicating VEGF, EGF, hepatocyte growth factor, interleukin-␤, tumor necrosis factor-␣, and CXCR4 secretion. 51 This leads to favor vascular repair and neovascularization. (Illustration credit: Cosmocyte/Ben Smith).…”
Section: Effects Of Exosome-like Microvesicles On Angiogenesismentioning
confidence: 99%
“…Опосредованное микро-частицами тромбоцитов фосфорилирование Akt наблюдается также в ýндотелиальных клетках. Показана повышенная регенерация ýндотелиоци-тов после инъекции обработанных микрочасти-цами ранних генераций ýндотелиоцитов (ýндоте-лиальных предшественников) в сонную артерию мыши при повреждении [72]. Кроме того, акти-вированные тромбоциты выделяют медиаторы с антиапоптотическим действием, такие как HGF, SDF-1, серотонин, аденозиндифосфат и сфинго-зин-1-фосфат, несущие сигналы к выживанию ýндотелиоцитам и MSCs в местах повреждения сосудов.…”
Section: тромбоциты и регенерацияunclassified